2020
DOI: 10.1038/s41598-020-60664-5
|View full text |Cite|
|
Sign up to set email alerts
|

Amylin and pramlintide modulate γ-secretase level and APP processing in lipid rafts

Abstract: A major characteristic of Alzheimer's disease (AD) is the accumulation of misfolded amyloid-β (Aβ) peptide. Several studies linked AD with type 2 diabetes due to similarities between Aβ and human amylin. This study investigates the effect of amylin and pramlintide on Aβ pathogenesis and the predisposing molecular mechanism(s) behind the observed effects in TgSwDI mouse, a cerebral amyloid angiopathy (CAA) and AD model. Our findings showed that thirty days of intraperitoneal injection with amylin or pramlintide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 64 publications
(84 reference statements)
0
12
0
Order By: Relevance
“…The amylin receptor, a class B GPCR, is viewed as a plausible therapeutic target for AD based upon observations that modulation of this receptor by either synthetic amylin analogs or amylin antagonists confers improvement in spatial memory and learning [ 6 8 , 16 , 17 ]. In order to resolve the dichotomy of whether it is activation or blockade of the amylin receptor that holds promise as a therapeutic strategy, we used a genetic approach consisting of a deletion within one copy of an endogenous chromosomal locus.…”
Section: Discussionmentioning
confidence: 99%
“…The amylin receptor, a class B GPCR, is viewed as a plausible therapeutic target for AD based upon observations that modulation of this receptor by either synthetic amylin analogs or amylin antagonists confers improvement in spatial memory and learning [ 6 8 , 16 , 17 ]. In order to resolve the dichotomy of whether it is activation or blockade of the amylin receptor that holds promise as a therapeutic strategy, we used a genetic approach consisting of a deletion within one copy of an endogenous chromosomal locus.…”
Section: Discussionmentioning
confidence: 99%
“…High-speed AFM (HS-AFM) enabled the kinetic measurement of the structural dynamics of biological molecular processes [79][80][81][82][83][84] including amyloid aggregation [93,[108][109][110][111][112][113][114][115][116]. Here, we show that HS-AFM links structural and dynamics studies, reviewing recent HS-AFM studies and including our findings for Aβ42 [93] and amylin [116], which is associated with not only type II diabetes but also AD [117][118][119][120][121][122][123].…”
Section: Introductionmentioning
confidence: 64%
“…Amylin crosses the blood-brain barrier (BBB) [157][158][159], and its aggregate deposition is found in the brains of type II diabetes patients with AD [121]. The mechanisms underlying the pathological [122,123] and suppressive [117][118][119][120] effects of amylin to AD remain controversial [160].…”
Section: Aggregation Inhibition By Synthetic Polymersmentioning
confidence: 99%
“…A robust in uence of altered AMY/CTR signaling upon Aβ-directed pathogenesis is supported by improvements in memory and pathology scored in two independent lines of APP695 transgenic mice that have both different genetic backgrounds and different tempos of AD-related changes (13,14). Moreover, a recent study revealed that amylin and its synthetic analog, pramlintide, when administered to AD mice, result in increased Aβ production via upregulation of APP and its processing enzyme, γ-secretase (17).…”
Section: Discussionmentioning
confidence: 98%
“…The amylin receptor, a class B GPCR, is viewed as a plausible therapeutic target for AD based upon observations that modulation of this receptor by either synthetic amylin analogs or amylin antagonists, confers improvement in spatial memory and learning (6,7,8,16,17). In order to resolve the dichotomy of whether it is activation or blockade of the amylin receptor that holds promise as a therapeutic strategy, we used a genetic approach consisting of a deletion within one copy of an endogenous chromosomal locus.…”
Section: Discussionmentioning
confidence: 99%